Complex coacervation assisted by a two-fluid nozzle for microencapsulation of ginger oil: Effect of atomization parameters - Ferreira, Sungil [UNESP]; Nicoletti, Vania Regina [UNESP] (Elsevier, 2020)
This study investigates the influence of the atomization parameters on complex coacervation by atomization, and is following a preceding study that presented the technique and investigated the effects of formulation. Complex coacervated capsules were produced by atomization, using emulsions with 1 and 6%(w/w) of gelatin and ginger oil atomized over a 1%(w/w) solution of gum Arabic, at constant polymer ratio of 1:2 (gelatin:gum Arabic) at pH 3.5. The air velocity at the nozzle varied from 72 to 168 m/s and the emulsion velocity at the nozzle varied from 0.4 to 0.6 m/s, maintaining the air to liquid velocity ratio at 170, 220 and 270. The mean diameter of the microcapsules produced varied from 52 to 75 μm and no crosslinking agents were used. The influence of atomization numbers Weber (We) and Ohnesorge (Oh), shear rate and shear stress on the encapsulation performance was carried out and a proposed model was able to predict the final size of the microcapsules produced at We ≥ 180 and Oh = 0.063. Encapsulation efficiency varied from 9 to 95%, and encapsulation yield varied from 50 to 99%. Finally, optimum conditions based on size prediction and microencapsulation parameters were proposed.
Keywords: Encapsulation efficiency; Encapsulation yield; Gelatin; Gum Arabic; Ohnesorge number; Particle size; Weber number